2012
DOI: 10.3109/14767058.2012.683085
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of chocolate on human pregnancy: a randomized controlled trial

Abstract: A modest daily intake of high-cocoa-content chocolate contributes to reduce blood pressure, glycemic and liver pattern during pregnancy without affecting the weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…According to the authors, unmeasured confounding or reverse causation may account for the positive association previously reported as discussed above. A non-placebo, controlled, non-blinded study by Di Renzo et al [13] suggested that modest daily intake of high-cocoa content chocolate contributes to BP reduction during pregnancy. The results of these epidemiologic studies reinforce the importance to assess the effect of chocolate consumption using a clinical trial design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors, unmeasured confounding or reverse causation may account for the positive association previously reported as discussed above. A non-placebo, controlled, non-blinded study by Di Renzo et al [13] suggested that modest daily intake of high-cocoa content chocolate contributes to BP reduction during pregnancy. The results of these epidemiologic studies reinforce the importance to assess the effect of chocolate consumption using a clinical trial design.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this association was not found in another case–control study [12]. Finally, a non-placebo, controlled, non-blinded study by Di Renzo et al [13] suggested that modest daily intake of high-cocoa content chocolate contributes to BP reduction during pregnancy.…”
Section: Introductionmentioning
confidence: 98%
“…Ellinger et al (2012) concluded that even a daily dose as low as 25 mg of epicatechin derived from a cocoa product was associated with a remarkable BP decrease which might be consistent with a decreased CV risk. Di Renzo and coworkers observed a BP decrease in pregnant women consuming daily 30 g of dark chocolate with 13 mg of monomeric flavanols (Di Renzo et al, 2012). These overall conclusions must, however, be examined very carefully.…”
Section: The Effect Of Cocoa On CV Risk Factorsmentioning
confidence: 99%
“…Abstention from alcohol, smoking cessation, exercises for the maintenance of fitness, calcium supplementation, and stress reduction, among others are recommended to prevent preeclampsia and its complications. Some studies have found a significant reduction of blood pressure with daily intake of chocolate, resulting in a reduced risk of gestational hypertension and preeclampsia [71], [72]. Although previous research have found a positive influence of physical activity on pregnant women and their infants [73][74][75], there is a lack of clinically-validated research aimed to determine the influence of exercise on risk of hypertensive disorders.…”
Section: Data Extractionmentioning
confidence: 97%